2007
DOI: 10.1016/j.cell.2007.10.054
|View full text |Cite
|
Sign up to set email alerts
|

let-7 Regulates Self Renewal and Tumorigenicity of Breast Cancer Cells

Abstract: Cancers may arise from rare self-renewing tumor-initiating cells (T-IC). However, how T-IC self renewal, multipotent differentiation, and tumorigenicity are maintained remains obscure. Because miRNAs can regulate cell-fate decisions, we compared miRNA expression in self-renewing and differentiated cells from breast cancer lines and in breast T-IC (BT-IC) and non-BT-IC from 1 degrees breast cancers. let-7 miRNAs were markedly reduced in BT-IC and increased with differentiation. Infecting BT-IC with let-7-lentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
1,539
6
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,744 publications
(1,624 citation statements)
references
References 33 publications
51
1,539
6
16
Order By: Relevance
“…Of the four most effective miRNAs identified, let-7c and miR200b belong to the let-7 and miRNA-200s families, respectively, of which the tumour-suppressor roles in TICs have been well appreciated 8,23,46 , while miR-222 and miR-424 were first identified as TIC-suppressing miRNAs despite a tumoursuppressor role of both miRNAs has been identified in a number of cancers other than HCC [47][48][49][50] . Paradoxically, miR-222 was previously regarded as oncogene in some reports because it could enhance some tumour cell growth by targeting CDK inhibitor p27 in vitro, and was found to be upregulated in HCC and some other types of cancers 42,51,52 ; however, its tumourpromoting role was rarely validated in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four most effective miRNAs identified, let-7c and miR200b belong to the let-7 and miRNA-200s families, respectively, of which the tumour-suppressor roles in TICs have been well appreciated 8,23,46 , while miR-222 and miR-424 were first identified as TIC-suppressing miRNAs despite a tumoursuppressor role of both miRNAs has been identified in a number of cancers other than HCC [47][48][49][50] . Paradoxically, miR-222 was previously regarded as oncogene in some reports because it could enhance some tumour cell growth by targeting CDK inhibitor p27 in vitro, and was found to be upregulated in HCC and some other types of cancers 42,51,52 ; however, its tumourpromoting role was rarely validated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, aberrant expression of miRNAs such as let-7, miR-34a, miR-181a, miRNA-130b in TICs has been found in a variety of tumour types. These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] .…”
mentioning
confidence: 99%
“…For example, lethal‐7a (let‐7a), one of the founding members in the miRNA family,3 is poorly expressed in human cancers including prostate, breast, and brain cancers, which is decreased by more than threefold in contrast to other healthy tissues. [[qv: 2b,4]] Accordingly, upregulation of let‐7a results in a marked promotion of apoptosis and inhibition of the proliferation and metastasis of cancer cell by silencing KRAS and high‐mobility group AT‐hook 2 (HMGA2) 5. Therefore, miRNA replacement therapies can be employed as a promising treatment strategy if the miRNA can be delivered to cancer cells with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Since in both studies let-7 miRNA was delivered at the same time as tumorigenesis was initiated, these two studies showed that let-7 can be used as a preventive therapy against lung cancer in the LSL-Kras G12D mice. In a similar experiment using let-7 treatment, Yu et al (2007a) showed that in a xenograft model of breast cancer, tumor-initiating cells, SK-3rd cells infected with lentivirus expressing let-7, developed significantly fewer tumors than cells given the control virus.…”
Section: Mirnas As Therapeuticsmentioning
confidence: 97%